Sufi Lifestyle, Spiritual Resilience, and Social Welfare (Psychospiritual and Metabolic Pathways to Community Health in the COVID-19 Era) - Budi Rahman Hakim (Pusat Riset dan Inovasi Nasional, 2022)
This study explores how the Qadiriyya–Naqshbandiyya Suryalaya Sufi Order (TQN Suryalaya) integrates spiritual practice and metabolic health to strengthen community resilience during the COVID-19 pandemic. While global health responses have largely focused on biomedical interventions, this research emphasizes the complementary role of faith-based practices in promoting holistic well-being. Using a qualitative methodology—including in-depth interviews, participant observation, and document analysis of the 2020 Maklumat and Abah Aos’s letter to the President—the study identifies two interrelated pathways that underpin the Sufi lifestyle. The psychospiritual pathway encompasses the reduction of death anxiety through tawakkul (trust in God) and riḍā (contentment), emotional stability via dhikr (remembrance of God) and muraqabah (mindful awareness), and theological framing that interprets fear of Allah as the ultimate form of protection. These practices helped practitioners reframe pandemic-related uncertainties, mitigate stress, and foster emotional resilience. The metabolic pathway involves dietary simplicity, moderated caloric intake, physical worship routines, stress management, and structured sleep hygiene. Together, these elements supported immune competence and physical health, aligning with contemporary models of psychoneuroimmunology and holistic health promotion. Findings reveal that the TQN lifestyle does not only enhance individual mental well-being but also fosters social solidarity through communal worship, mutual aid, and spiritual counseling, thereby functioning as a culturally embedded form of faith-based social welfare. The study highlights the policy potential of incorporating Sufi practices into community health strategies and enriches interdisciplinary literature on religion, resilience, and social welfare. This dual-pathway model demonstrates that Sufi traditions can play a critical role in mitigating both the psychological and physiological impacts of global crises.